Analisis Supply Chain Produksi Komoditas Bawang Merah: Kajian Literatur - Daffa Rasyid Rabbani; Alyonan Raihan Hilmy H; Hazila Liska Putri; Jonathan Vito Sebastian (Journal of Business Economics and Management | E-ISSN : 3063-8968, 2026)
This study analyzes the supply chain of shallot (Allium ascalonicum L.) production through a qualitative literature review approach. The study aims to examine the structure and flow of the production-stage supply chain, identify factors influencing supply chain performance at the farmer level, analyze dominant production risks, and evaluate performance based on efficiency, productivity, and sustainability aspects. Data were obtained from scientific articles, national and international journals, and other relevant academic publications related to agribusiness supply chains and shallot production. The findings indicate that the supply chain structure varies across production centers. Grobogan and Bantul show multi-tiered distribution patterns involving farmers, collectors, wholesalers, and retailers, while Brebes demonstrates a more vertically integrated agroindustry model where farmers directly supply processing industries. Supply chain performance at the production stage is influenced by cultivation technology, agroclimatic variability, institutional capacity, and socio-demographic characteristics of farmers. Major risks include climate uncertainty, seed quality issues, pest and disease attacks, input price fluctuations, and limited access to market information. Strengthening farmer coordination, adopting adaptive cultivation technologies, and developing structured partnerships are essential strategies to improve supply chain efficiency, productivity, and sustainability.